Islamic Studies And Private Universities In South-West Nigeria: Challenges And Prospects - Adenigba, Sikiru; Hassan , Yoosuf Akorede (Al-Basirah Journal, 2023)
Islamic Studies is one of the core and pertinent courses offered and taught at both private and public universities in Nigeria. The subject prepared its graduates to have potentialities, capabilities manpower in teaching, administration, politics, economic, legislation and judiciary in Nigeria. Despite these significant contributions, the subject has confronted with a lot of deprivations in the enrollment of students, recruitment of staff and availability of physical and instructional materials. Based on these, the paper therefore, intends to explore the teaching and learning of Islamic studies in the south west Nigeria private universities, identify problems facing its teaching and learning and proffer solutions to these predicaments. The methodology adopted was historical and analytical design with information from both oral interview and written sources from libraries in Nigeria. Among the findings of the study are that the Subject-Islamic studies needs more experts to teach its core courses in private universities in Nigeria and students who wish to enroll for the subject should have rudiments of the discipline before admission.